Biotope City Wienerberg. Ein neuer Stadtteil für Wien mit einem neuen Leitbild. - Reinwald, Florian; Ring, Zita; Damyanovic, Doris (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
In the light of climate change and urban densification, new and innovative solutions for urban and landscape planning are necessary. The urban guiding principle of Biotope City is a forward-looking answer to these changed framework conditions of urban housing in the face of climate change. The paper provides some insights into the development of the "Biotope City Wienerberg" - the first implementation of the guiding principle of Biotope City in the development of new urban quarter.
Keywords: Stadtteilplanung; Bauen(klimagerecht); Klimaanpassung; Nachhaltige Stadtentwicklung; Landschaftsplanung; Freiraumplanung; Modellprojekt; Ökosystemleistung; Gebäudebegrünung; Städtebauliches Leitbild; Grüne Infrastruktur